Driving factors of growth in Hungary - a decomposition exercise - Gábor Kátay; Zoltán Wolf (Magyar Nemzeti Bank, 2008)
Applications tend to ignore that measured TFP reflects the variation of output that cannot be explained by changes in inputs. Such a change is not necessarily technological, so measured TFP differences across firms are an amalgam of technological, efficiency and other differences in attributes, which calls for further refinement in the treatment of TFP. To control for cyclical effects, we modify a standard technique in firmlevel production function estimation using a capacity utilization proxy. Based on a large panel of Hungarian manufacturing firms, we decompose value added growth to input factor, capacity utilization and estimated TFP growth contributions. We find that using an hours worked proxy, the variance of the residual drops considerably. We also find that TFP's role has not been stable over the period: it contributed to value added growth mostly in periods when/after institutional reforms, privatization or FDI inflow took place and lost its importance several years after the shocks.
Keywords: C14; C23; D24; O12; O47; 330; economic growth; production function; input factor contributions; total factor productivity; capacity utilization; aggregation; panel data; Wirtschaftswachstum; Produktivität; Produktionsfunktion; Kapazitätsauslastung; Schätzung; Ungarn